2019
DOI: 10.33423/ajm.v19i3.2188
|View full text |Cite
|
Sign up to set email alerts
|

In Extremis Leadership: A Study of the Effects in Different Contexts

Abstract: When lives are at stake, astutely reading a situation (situation awareness) and belief in one's ability to manage it (self-efficacy) are crucial leadership skills. Fire fighters, law enforcement officers and military leaders routinely enter dangerous, in extremis, situations. Data from these environments is difficult to capture, so there is a gap in the literature looking at the distinctness of these professions. We report on a survey of 514 military, firefighting, and law enforcement leaders examining their e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 68 publications
0
2
0
Order By: Relevance
“…To address this in policing it is necessary to briefly revisit TMT research into the actions of military soldiers. High self-esteem and combat experience helped soldiers suppress mission terror (van den Berg and Soeters, 2009), and was related to situational awareness (Dixon et al, 2019). Further, repeated, and realistic training provided a pre-battle mindset that protects from debilitating paralysis (Grossman and Christensen, 2022;Ripley, 2008;Sharps, 2010).…”
Section: Police Training: Danger and Safety As Cultural Dimensionsmentioning
confidence: 99%
See 1 more Smart Citation
“…To address this in policing it is necessary to briefly revisit TMT research into the actions of military soldiers. High self-esteem and combat experience helped soldiers suppress mission terror (van den Berg and Soeters, 2009), and was related to situational awareness (Dixon et al, 2019). Further, repeated, and realistic training provided a pre-battle mindset that protects from debilitating paralysis (Grossman and Christensen, 2022;Ripley, 2008;Sharps, 2010).…”
Section: Police Training: Danger and Safety As Cultural Dimensionsmentioning
confidence: 99%
“…A 2009 study reported that soldiers who possessed high self-assessment of their unit's performance (a proxy measure for personal self-esteem), as well as respondents who belonged to units with combat experience, helped to suppress the natural terror of their mission (van den Berg and Soeters, 2009). Others have reported that higher levels of self-esteem were significantly related to an increase in situational awareness within a combat setting, and that soldiers felt that risks in that setting were manageable (Dixon et al, 2019).…”
Section: Terror Management Theorymentioning
confidence: 99%